Pengaruh Komunikasi, Pendidikan dan Pelatihan, Rekrutmen dan Seleksi Terhadap Peningkatan Kinerja Karyawan di Bank Mandiri dengan Komitmen Karyawan Sebagai Variabel Intervening - Pungky Namira (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Human Resource Management is now seen as one of the main factors that differentiate between successful and unsuccessful organizations after technology or finance. The purpose of this research is to find out and analyze the effect of communication on employee commitment, to know and analyze the effect of communication on improving employee performance, to know and analyze the effect of education and training on employee commitment, to know and analyze the effect of education and training on improving employee performance., to know and analyze the effect of recruitment and selection on employee commitment, to know and analyze the effect of recruitment and selection on employee performance improvement, and to know and analyze the effect of employee commitment on employee performance improvement. The research method taken is a causative quantitative descriptive research method. The population taken is Bank Mandiri employees in Bekasi. The samples to be taken are one hundred employees of Mandiri Banks in Bekasi City. In this study, exogenous latent variables are communication, education and training, recruitment, and selection. While endogenous latent variables are employee commitment, employee performance improvement. The results of research it can be concluded that: there is no influence and no significant communication with employee commitment, there is no influence and no significant communication with improving employee performance, there is no significant but significant effect of education and training on employee commitment, there is no significant influence but education and training with increasing employee performance, there is no significant influence and recruitment and selection on employee commitment, there is no effect and no significant recruitment and selection on employee performance improvement, there is no significant effect but employee commitment to increased employee performance. Meanwhile, when they wanted to analyze using the SEM AMOS 24 application, it was said that the data was unobservable.